2018
DOI: 10.1089/mab.2018.0025
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Critical Epitope of Anti-Rat Podoplanin Monoclonal Antibody PMab-2

Abstract: Rat podoplanin (rPDPN) is a recognized lymphatic endothelial cell marker and is expressed on the podocytes of kidney and type I lung alveolar cells. rPDPN is a type I transmembrane sialoglycoprotein and induces platelet aggregation via the C-type lectin-like receptor-2 of platelets. It comprises four platelet aggregation-stimulating (PLAG) domains: PLAG1–3, present in the N-terminus, and PLAG4, in the center of the PDPN protein. Previously, we developed a mouse anti-rPDPN monoclonal antibody clone, PMab-2, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Conversely, the binding epitopes of mAbs produced by immunizing with synthesized peptides have been easily determined using deletion mutants and point mutants of synthesized peptides. (29,30) We first synthesized a series of tigPDPN peptides, which are summarized in Table 1. Using ELISA, PMab-231 detected 24-43 peptides corresponding to the 24th-43rd amino acids (aas) of tigPDPN.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the binding epitopes of mAbs produced by immunizing with synthesized peptides have been easily determined using deletion mutants and point mutants of synthesized peptides. (29,30) We first synthesized a series of tigPDPN peptides, which are summarized in Table 1. Using ELISA, PMab-231 detected 24-43 peptides corresponding to the 24th-43rd amino acids (aas) of tigPDPN.…”
Section: Resultsmentioning
confidence: 99%
“…(22,34,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) These epitope mapping results showed that almost all anti-PDPN mAbs react with PLAG domains or PLDs. (7,(39)(40)(41)43,44,(49)(50)(51) The critical epitope of PMab-237 was also shown to be located in PLD (Fig. 4), suggesting that PLAG domains and PLD were advantageous to the epitope for several applications such as flow cytometry, western blotting, and immunohistochemical analyses.…”
Section: Discussionmentioning
confidence: 97%
“…(31,32) We have established different anti-PDPN mAbs for many species by employing a cell-based immunization and screening (CBIS) method, and characterized the targeted epitopes. (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47) Recently, we developed a novel anti-PDPN mAb, clone PMab-269 (mouse IgG 1 , kappa), which recognizes the California sea lion (Zalophus californianus) PDPN (seaPDPN). (48) The PMab-269 clearly detected seaPDPN protein in flow cytometry and Western blotting analysis.…”
Section: Introductionmentioning
confidence: 99%